Post-pandemic Travel Decisions on Domestic Tourism Destinations for Young People - Feronica Simanjorang; Marlina, Deliana (Journal of Sumatera Sociological Indicators, 2025)
The tourism sector is one of the largest industrial sectors and drivers of the world economy that is vulnerable to disasters. The spread of covid-19 causes tourist destinations to rely heavily on the presence of domestic tourists, especially for safety and health reasons for the younger generation. This research aims to understand the travel decisions of the younger generation after the pandemic in domestic tourist destinations. This research is qualitative in nature with a case study approach. Researchers determined informants who are members of the Millennial Generation and Generation Z by conducting in-depth interviews and collecting secondary data through informants' personal social media. The research results are divided into three phases, namely the pre-travel phase, the phase during the trip, and the post-travel phase. The researcher concluded that after the Covid-19 pandemic, there was a change in the decision-making process of young people who were influenced by social media.